1996
DOI: 10.1007/bf00214704
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages during avian optic nerve development: relationship to cell death and differentiation into microglia

Abstract: Cell death is frequent during the development of the nervous system. In the developing optic nerve of chicks and quails, neuroepithelial cell death was first observable on the third day of incubation, slightly after the first cell ganglion axons appeared in the stalk. Specialized phagocytes were observed within the stalk in chronological and topographical coincidence with cell death. These cells were identified as macrophages because of their morphological features, intense acid phosphatase activity and, in qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…The definitive characterization of cathepsin B/ D-expressing cells was confirmed by their histochemical labeling with TL that recognizes macrophage/microglial cells in the nervous system of rodents (Acarin et al, 1994;Santos et al, 2008). Furthermore, in most cases, cathepsin B/D-expressing cells were in chronotopographical coincidence with regions affected by extensive cell death during development, as has been shown for cell death and macrophage/microglial precursors in the nervous parenchyma (Hume et al, 1983;Navascues and MartinPartido, 1990;Martin-Partido et al, 1991;Perry et al, 1993;Moujahid et al, 1996;Rodriguez-Gallardo et al, 2005;Santos et al, 2008).…”
Section: Cathepsin B and D Expression In Macrophages And Microglial Pmentioning
confidence: 67%
See 4 more Smart Citations
“…The definitive characterization of cathepsin B/ D-expressing cells was confirmed by their histochemical labeling with TL that recognizes macrophage/microglial cells in the nervous system of rodents (Acarin et al, 1994;Santos et al, 2008). Furthermore, in most cases, cathepsin B/D-expressing cells were in chronotopographical coincidence with regions affected by extensive cell death during development, as has been shown for cell death and macrophage/microglial precursors in the nervous parenchyma (Hume et al, 1983;Navascues and MartinPartido, 1990;Martin-Partido et al, 1991;Perry et al, 1993;Moujahid et al, 1996;Rodriguez-Gallardo et al, 2005;Santos et al, 2008).…”
Section: Cathepsin B and D Expression In Macrophages And Microglial Pmentioning
confidence: 67%
“…This morphology is maintained at postnatal stages. These morphological changes have also been observed in the developing avian optic nerve (Moujahid et al, 1996). Those authors suggested that macrophages show different morphological features due to the changes in the cell environment during the optic stalk-optic nerve transition, passing from a neuroepithelial to a fibrous environment.…”
Section: Spatiotemporal Distribution Of Cathepsin B/d-expressing Macrmentioning
confidence: 71%
See 3 more Smart Citations